THE PRESTIGE OF BATU NA PIR AS A MEANS OF IMPROVING THE SOCIAL STATUS OF THE BATAK TOBA COMMUNITY IN SILALAHI II VILLAGE, NORTH SUMATRA - Limbong, Angli Rosalia; Zuryani, Nazrina; Krisna Aditya, I Gst. Ngr Agung; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 4 No 2 (2024): JISSOROT, 2025)
This study examines the tradition of building "batu na pir" in Silalahi II Village as a means of enhancing the social status of the local community. The research aims to analyze the prestige associated with batu na pir, employing an exploratory qualitative method with the theoretical framework of habitus, arena, and capital by Bourdieu. The findings reveal that batu na pir, which serves as a repository for the remains of ancestors, is a longstanding tradition of the Batak Toba people, maintained due to their strong belief in the power of ancestral spirits. The size and grandeur of batu na pir play a significant role in elevating the social status of its owner, leading the community to compete in constructing larger and more luxurious batu na pir. This study recommends education to prevent unhealthy competition and emphasizes the importance of preserving the tradition's original purpose as a form of respect for ancestors. Keywords : Prestige, Batu na pir, Social status, Batak Toba community